Digital Literacy Paradox: Moderating Effects on E-Commerce Adoption and Financial Planning Among MSMEs - Dedi Hariyanto; Heni Safitri (School of Business, IPB University (SB-IPB), 2026)
Background: Micro, Small, and Medium Enterprises (MSMEs) in West Kalimantan face substantial financial management challenges amid accelerating digital transformation. As a border province geographically distant from Indonesia’s primary economic centers, Pontianak’s entrepreneurial ecosystem is characterized by informal financial practices, uneven digital infrastructure and limited access to formal financial services. These structural conditions create disparities in financial capability and digital readiness among MSME actors.Purpose: This study examines the effects of financial behavior, fintech development, online shopping platforms, and present bias on MSMEs’ financial planning, with digital literacy as a moderating variable within an integrated behavioral–technological framework.Methods: A quantitative causal research design was employed using structured online questionnaires distributed to 262 MSME owners selected through purposive sampling. Six validated constructs were measured using a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 to assess both direct and moderating effects.Results: Financial behavior was the strongest predictor of financial planning, followed by online shopping platform utilization and fintech development. The present bias did not have a significant direct effect. Digital literacy showed no direct influence on financial planning; however, it negatively moderated the relationship between online shopping platforms and financial planning, indicating diminishing marginal returns of e-commerce utilization among MSMEs with higher digital capabilities.Conclusion: Behavioral financial discipline remains the cornerstone of MSME financial planning, regardless of technological sophistication. Digital tools contribute to financial planning when they are integrated with structured managerial practices rather than functioning as standalone solutions.Originality/value: This study extends behavioral finance and technology adoption theories within the urban entrepreneurial ecosystem of Pontianak. The identification of a negative moderating effect of digital literacy reveals non-linear and context-dependent dynamics between digital capability and financial planning outcomes, offering policy-relevant insights into inclusive digital transformation strategies in developing urban economies. Keywords: digital literacy, e-commerce, financial behavior, financial planning, fintech